2010
DOI: 10.1111/j.1465-3362.2010.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of parents, siblings and peers on pre- and early-teen smoking: A multilevel model

Abstract: Cross-level interactions were generally non-significant. Early teenage smoking was best explained by sibling and peer smoking, and individual risks largely accounted for the substantial variation observed across schools and communities. In terms of future tobacco control, findings point to the utility of targeting families in disadvantaged communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 42 publications
(55 reference statements)
6
44
3
3
Order By: Relevance
“…Consistent with previous research, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] parental smoking was strongly associated with adolescent smoking. Interestingly, children of both parents who were late-onset persistent smokers (ie, they had a low probability of smoking in their teenage years that increased in adulthood) or who had a history of light smoking in adolescence that declined in adulthood (ie, the early-onset light smokers who quit/ reduced) had a significantly higher risk of smoking than children of parents who did not smoke in adolescence or adulthood.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous research, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] parental smoking was strongly associated with adolescent smoking. Interestingly, children of both parents who were late-onset persistent smokers (ie, they had a low probability of smoking in their teenage years that increased in adulthood) or who had a history of light smoking in adolescence that declined in adulthood (ie, the early-onset light smokers who quit/ reduced) had a significantly higher risk of smoking than children of parents who did not smoke in adolescence or adulthood.…”
Section: Discussionsupporting
confidence: 90%
“…5 Although cross-sectional, [6][7][8][9][10][11] follow-up, [12][13][14][15] and longitudinal [16][17][18] studies of adolescents have shown a relationship between parental and child smoking, the overall body of research remains equivocal. 5 Previous studies have been limited by the use of retrospective reports of parent smoking, the use of offspring reports of parental smoking and other parent-level risk factors, and the lack of detailed measures encompassing the duration and intensity of parental cigarette use.…”
Section: Discussionmentioning
confidence: 99%
“…While compared to smoker group, participants were recruited in various locations in Kota Bharu, Kelantan, Malaysia. This supports the interpretation that the community and school level variables are predictive of adolescent smoking [19]. School achievement has been shown to be a strong predictor of smoking behavior [20].…”
Section: Resultssupporting
confidence: 83%
“…There is strong evidence that parental disapproval, monitoring and family conflict are each strongly related to adolescent use of a specific drug Kelly et al, 2011;Ryan, Jorm, & Lubman, 2010), and there is some evidence that these parental factors can also mitigate the influence of peers who use substances (Marschall-Lévesque, Castellanos-Ryan, Vitaro, & Séguin, 2014). However, this moderating effect of parents on peer influence was not examined in the context of polysubstance use.…”
Section: Introductionmentioning
confidence: 99%